MicroRNAs and in kidney function and disease - Akkina, Sanjeev (2011)
MicroRNAs (miRNA) are short non-coding RNA sequences that regulate gene expression by blocking protein translation or inducing mRNA degradation. miRNA is found in various tissues with variable expression and changes in expression are related to various disease processes. Evidence suggests that changes in miRNA expression are critical for the normal development of kidney tissue. Alternatively, in diseases such as diabetic nephropathy, polycystic kidney disease, and lupus nephritis, specific miRNAs may enhance disease manifestations in a myriad of ways, ranging from activation of fibrotic pathways to anatomical changes that abet proteinuria. The variable expression of miRNA in kidney tissue, whether in the context of normal development or disease processes, makes miRNAs a valuable new tool for understanding, diagnosing, and discovering therapeutic options for pathological processes that affect the kidney.